Europe, Regions and European Regionalism - Scully, Roger. author. aut Link
X, 277 p.
Keywords: Europe, Regions and European Regionalism examines the political role of regions and regionalism within contemporary Europe. Offering an up-to-date analysis of regionalism with a broad empirical scope, this book explores regions and regionalism in the period after the substantial enlargements of the European Union.